2022
DOI: 10.1155/2022/1016692
|View full text |Cite
|
Sign up to set email alerts
|

The Public Opinion Evolution under Group Interaction in Different Information Features

Abstract: Before expressing opinions, most people usually consider the standpoint of their friends nearby to avoid being isolated, which may lead to the herding effect. The words of celebrities in social networks usually attract public attention and affect the opinion evolution in the entire network. This process also causes the similar status quo. In this study, we find that the key figures play the guiding roles in public opinions who undertake the group pressure from information amount. Therefore, we build the cost f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…We found no discernible impact of authoritative figures (experts) on shaping public opinion during martial law, which would contradict other researchers' findings (Wei et al, 2022). We explain this trend by the depreciation of the expert-analyst's figure in modern Ukrainian society due to the consistently inaccurate predictions regarding the progression of events.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…We found no discernible impact of authoritative figures (experts) on shaping public opinion during martial law, which would contradict other researchers' findings (Wei et al, 2022). We explain this trend by the depreciation of the expert-analyst's figure in modern Ukrainian society due to the consistently inaccurate predictions regarding the progression of events.…”
Section: Discussioncontrasting
confidence: 96%
“…The key factors of shaping public sentiment are as follows: information, media, social interaction, education and life experience of members of society, the social and political context of interaction, emotions, and values of participants in interaction (Ausat, 2023). As noted by Wei et al (2022), authoritative public figures known to the general public significantly influence public opinion. The experimental confirmation of the influence exerted by both the majority and expert opinion on forming a collective stance towards certain phenomena was shown (Moussaïd et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Mansouri and Taghiyareh [82] show that when influential leaders exist in a social network, segregation has less impact on opinion formation than the effect created by INFLs. This shows how INFLs are key drivers of belief change in opinion networks [97], including public opinion formation [92]. This effect was also verified when mass media played the role of INFLs [84].…”
Section: Opinion Dynamics Dimensionmentioning
confidence: 53%
“…In emergency situations, network-based emergency response has more advantages than traditional hierarchical response [23]. Wei et al [24] constructed a cost function for public opinion change and studied the evolution law of public opinion based on the scope and amount of information dissemination by public figures. They found that key figures play a guiding role in public opinion, and they bear group pressure from the amount of information.…”
Section: Public Opinion and Social Network Analysismentioning
confidence: 99%